The life and thought of Herbert Butterfield: history, science, and God - Bentley, Michael (Cambridge Univ. Press, 2011)
"Once recalled only for The Whig interpretation of history (1931) and Christianity and history (1949), Sir Herbert Butterfield's contribution to western culture has undergone an astonishing revaluation over the past twenty years. What has been left out of this reappraisal is the man himself. Yet the force of Butterfield's writings is weakened without some knowledge of the man behind them: his temperament, contexts, and personal torments. Previous authors have been unable to supply a rounded portrait for lack of available material, particularly a dearth of sources for the crucial period before the outbreak of war in 1939. Michael Bentley's original, startling biography draws on sources never seen before. They enable him to present a new Butterfield, one deeply troubled by self-doubt, driven by an urgent sexuality and plagued by an unending tension between history, science and God in a mind as hard and cynical as it was loving and charitable"--